2018
DOI: 10.1177/0091450917748163
|View full text |Cite
|
Sign up to set email alerts
|

“Getting Better”

Abstract: The alcohol and other drug field is characterized by great diversity in kinds of treatment and treatment philosophies. Even the kinds of problems treatment is expected to address vary significantly, although agreement seems to exist that the general purpose is to help people "get better." This article considers this diversity, drawing on a qualitative project conducted in three countries: Australia, Canada, and Sweden. Inspired by the project's multisite approach and the questions it raises about comparative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…In an early study, Berg (1996) showed that the medical record is not just a container of patient information; it also shapes the very nature of medical practice. Similarly, research has shown that different treatment techniques typically individualise addiction problems and make strong assumptions about what is considered healthy and normal (Dennis, 2017(Dennis, , 2020Fomiatti et al, 2017;Fraser & Ekendahl, 2018;Pienaar et al, 2017). We follow this analytical path and target what objects or entities 'become' through practice, which makes redundant any separation of the entity 'itself' and its discursive representations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In an early study, Berg (1996) showed that the medical record is not just a container of patient information; it also shapes the very nature of medical practice. Similarly, research has shown that different treatment techniques typically individualise addiction problems and make strong assumptions about what is considered healthy and normal (Dennis, 2017(Dennis, , 2020Fomiatti et al, 2017;Fraser & Ekendahl, 2018;Pienaar et al, 2017). We follow this analytical path and target what objects or entities 'become' through practice, which makes redundant any separation of the entity 'itself' and its discursive representations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons used in accounts can shed light on what key assumptions people have about their lives and living conditions, but they also give us the opportunity to ponder upon what realities they leave out (Fraser & Ekendahl, 2018;Seear et al, 2020). Our analysis reveals that the young people in their comparisons drew on culturally, institutionally and organizationally naturalized narratives about cannabis having objective drug effects, the individual being responsible and autonomous and the persistent risk of use getting out of control.…”
Section: Discussionmentioning
confidence: 92%
“…Comparison is a fundamental tool used by people to orient themselves in the world -'[w]e are all comparativists' as French philosopher Isabelle Stengers puts it in an article on the topic (Stengers, 2011, p. 48; see also Fraser & Ekendahl, 2018). We make comparisons all the time, and it would be difficult to understand ourselves and our lives without them.…”
Section: Comparison As a Tool In Identity Formationmentioning
confidence: 99%
See 2 more Smart Citations